PERAN PERPUSTAKAAN SEBAGAI SARANA PENDUKUNG GERAKAN LITERASI SEKOLAH DI SD MUHAMMADIYAH PAKEM - Saifudin, Muhamad Fakhrur; Istiqomah, Alifiyah Nur (JRPD (Jurnal Riset Pendidikan Dasar), 2021)
This study describes the role and strategy of the library as a means of supporting the literacy school movement at SD Muhammadiyah Pakem Sleman. The method used in this research is the descriptive method. The research uses qualitative data and describes. Data collection techniques are interview, documentation, and observation. The data analysis technique used a qualitative descriptive analysis. The data validity technique used technical triangulation and source triangulation. The result showed that the role of the school library includes the role of education, the role of information, the role of administrative responsibility, the role of research, and the role of recreation. Educational role wich providing fiction and nonfiction books, information role by providing various information from various sources, administrative responsibility role by having rules and sanctions for users. The role as research that can be used to collect data and role of recreation which can be a good and interesting place. SD Muhammadiyah Pakem Sleman has implemented three stages of literacy movement, namely the habit stage by getting used to reading day, development stage by developing literacy activities and giving an appreciation of literacy skills in students, and a learning stage with a learning method that integrates literacy and involves the public to improve literacy skills.